Thrombectomy With and Without Computed Tomography Perfusion Imaging in the Early Time Window: A Pooled Analysis of Patient-Level Data. Issue 4 (30th November 2021) - Jadhav, Ashutosh P.; Goyal, Mayank; Ospel, Johanna; Campbell, Bruce C.; Majoie, Charles B.L.M.; Dippel, Diederik W.; White, Phil; Bracard, Serge; Guillemin, Francis; Davalos, Antoni; Hill, Michael D.; Demchuk, Andrew M.; et al.
Abstract : Background: The optimal imaging paradigm for endovascular thrombectomy (EVT) patient selection in early time window (0–6 hours) treated acute ischemic stroke patients remains uncertain. We aimed to compare post-EVT outcomes between patients who underwent prerandomization basic (noncontrast computed tomography [CT], CT angiography only) versus additional advanced imaging (computed tomography perfusion [CTP] imaging) and to determine the association of performance of prerandomization CTP imaging with clinical outcomes. Methods: The HERMES collaboration (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials) pooled patient-level data from randomized controlled trials comparing EVT with usual care for acute ischemic stroke due to anterior circulation large vessel occlusion. Good functional outcome, defined as modified Rankin Scale score 0 to 2 at 90 days, was compared between randomized patients with and without CTP baseline imaging. Univariable and multivariable binary logistic regression analysis was performed to determine the association of baseline CTP imaging and good functional outcome. Results: We analyzed 1348 patients 610 (45.3%) of whom underwent CTP prerandomization. The benefit of EVT compared with best medical management was maintained irrespective of the baseline imaging paradigm (90-day modified Rankin Scale score 0–2 in EVT versus control patients: with CTP: 46.0% (137/298) versus 28.9% (88/305), without CTP: 44.1% (162/367) versus 27.3% (100/366). Performance of CTP baseline imaging compared with baseline noncontrast CT and CT angiography only yielded similar rates of good outcome (odds ratio, 1.05 [95% CI, 0.82–1.33], adjusted odds ratio, 1.04, [95% CI, 0.80–1.35]). Conclusions: Rates of good functional outcome were similar among patients in whom CTP was or was not performed, and EVT treatment effect in the 0- to 6-hour time window was similar in patients with and without baseline CTP imaging.